2020
DOI: 10.3390/ijerph17010330
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Facial Emotion Recognition and Mental Health in Early Adolescence

Abstract: Research shows that adolescents with mental illnesses have a bias for processing negative facial emotions, and this may play a role in impaired social functioning that often co-exists with a mental health diagnosis. This study examined associations between psychological and somatic problems and facial emotion recognition in early adolescence; as any processing biases in this age-group may be an early indicator of later mental illnesses. A community sample of 40 12-year-olds self-rated their symptoms of anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 36 publications
2
32
0
2
Order By: Relevance
“…In this work, we investigated the processing of fearful facial expressions in individuals recovered in COVID-19 post-intensive care units, through a behavioral approach. As reported in previous studies (i.e., [9,10,28]), an altered recognition of facial emotion expressions represents a sign of mental health difficulties [18,19] and psychological distress [14]. We observed an alteration of this process in our sample: specifically, our participants reported difficulties in detecting and recognizing fearful expressions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this work, we investigated the processing of fearful facial expressions in individuals recovered in COVID-19 post-intensive care units, through a behavioral approach. As reported in previous studies (i.e., [9,10,28]), an altered recognition of facial emotion expressions represents a sign of mental health difficulties [18,19] and psychological distress [14]. We observed an alteration of this process in our sample: specifically, our participants reported difficulties in detecting and recognizing fearful expressions.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, fear and anxiety share the cerebral circuits (i.e., [14]). Altered recognition of facial emotion expressions has been suggested to be a sign of mental health difficulties [17][18][19] and psychological distress [14].…”
Section: Introductionmentioning
confidence: 99%
“…This association has been shown via increased accuracy of identification of fearful faces by individuals with high trait anxiety 64,65 (although other studies have failed to replicate this finding 66,67 ), and by increased accuracy of fearful face identification by healthy volunteers under threat of electrical shock, a condition that otherwise degrades accuracy of identification of neutral or happy faces 68 . A specific speeding of reaction time for identifying fearful faces has also been observed in adolescents with depressive and anxiety symptoms 69 .…”
Section: Discussionmentioning
confidence: 88%
“…GabrielleSimcock [25] et al have done a study, which examined the associations between psychological and physical problems and facial recognition in early adolescence. The computerized emotion recognition task are completed where they identi ed images of 40 faces that show expressions of anger, fear, sadness, happiness, or a neutral expression.The results showed that increased symptoms of anxiety, depression, and somatization were signi cantly associated with fewer correct responses to angry expressions.These symptoms have also been associated with the rapid and more accurate recognition of expressions of fear.…”
Section: Santhosh Kumar[18] Et Al Discussed Deep Learning Approach For Emotion Recognition From Human Bodymentioning
confidence: 99%